Enhanced Performance of Millimetre-Wave Dual-Polarized Antennas Through Reduced Element Spacing - Mohd Hamzah, Siti Zainab; Abdul Malek, Norun Farihah; Mohamad, Sarah Yasmin; Mohd Isa, Farah Nadia; Mohd Ramly, Athirah (International Journal of Integrated Engineering, 2025)
The increasing demand for higher data rates and better signal quality in 5G wireless networks has driven the advancement of dual-polarized antennas, which offer improved channel capacity and enhanced MIMO capabilities. Nevertheless, challenges such as achieving sufficient isolation, compact form factors, and effective beamforming remain, especially in millimeter-wave (mmWave) applications. This study introduces an enhanced single-layer, dual-polarized patch antenna with slant ±45° polarization, operating at 28 GHz. Designed to optimize performance while maintaining a compact structure, the antenna significantly reduces inter-element spacing — from approximately 57 mm to 15 mm. It is built on a Rogers RT5880 substrate and incorporates a T-power divider for efficient signal distribution. Both simulation and experimental results confirm improvements in reflection coefficient, radiation patterns, and gain compared to earlier designs. The antenna achieves a reflection coefficient of less than -10 dB, indicating strong performance, with measured gains ranging from 3.7 to 7.8 dBi. The revised radiation patterns display reduced sidelobe levels and a more directional main beam in the co-elevation azimuth plane, highlighting the effectiveness of the reduced spacing. These enhancements make the proposed design well-suited for 5G mmWave applications, particularly for beam-steering systems. Future developments can build on this work to further optimize performance in high-frequency wireless networks.